Antifungal Effect and Protective Role of Ursolic Acid and Three Phenolic Derivatives in the Management of Sorghum Grain Mold Under Field Conditions. Issue 9 (31st August 2016) - Shaik, Ameer Basha; Ahil, Sajeli Begum; Govardhanam, Ragavendra; Senthi, Mahibalan; Khan, Rukaiyya; Sojitra, Ravi; Kumar, Santhosh; Srinivas, Asalla
Abstract : In this study, investigation was carried out under in vitro as well as field conditions to explore inhibitors of sorghum grain mold. Phytochemicals, viz ., methyl trans ‐ p ‐coumarate (AIC‐1), methyl caffeate (AIC‐2), syringic acid (AIC‐3), and ursolic acid (UA), at different concentrations (500, 750, and 1000 ppm) were tested on spore germination of Alternaria alternata, Curvularia lunata, Fusarium moniliforme, F . pallidoroseum, and Helminthosporium sp. Significant growth inhibition ( P < 0.001) was observed against all fungi except A . alternata which was found to be resistant to AIC‐3. Further, two separate sets of field experiments involving spraying of water and F . moniliforme suspension over chemicals treated (1000 ppm) sorghum panicles were done. The levels of protection varied with different treatments which were graded using a standard 1 – 9 rating scale. The Fusarium ‐challenged panicles (FCP) showed lesser susceptibility and decreased the rate of infection of grain mold (grade 7.0), compared to simple UA, AIC‐2, and AIC‐1 treatments (7.4, 7.6, and 8.0 grade, resp.). The HPLC quantification of differentially induced phenolic acids in treated sorghum grains substantiated this effect disclosing the higher accumulation of chlorogenic, vanillic, and salicylic acids in FCP. This might be due to defensive induction of these acids by the plants. Although mold control by examined chemicals were lesser than the standard Tilt (grade 5.9), they were found to be nontoxic to mammalian cells under cytotoxicity assay. Abstract :